ChemInform Abstract: Bi2S3 Bipyramids in Layered Sulfides M2Bi2S3(AlCl4)2 (M: Ag, Cu). Issue 19 (May 2015) - Groh, Matthias F.; Knies, Maximilian; Isaeva, Anna; Ruck, Michael
Abstract: Polycrystalline Cu2 Bi2 S3 (AlCl4 )2 (I) and Ag2 Bi2 S3 (AlCl4 )2 (II) are prepared by solid state reaction of 2:1:2 molar mixtures of CuCl (AgCl), Bi2 S3, and AlCl3 (quartz ampoules, 200 °C, 7 d).